Matching frictions and distorted beliefs: Evidence from a job fair experiment - Girum Abebe; Stefano A. Caria; Marcel Fafchamps; Paolo Falco; Simon Franklin; Simon Quinn; Forhad Jahan Shilpi (Queen Mary University of London, School of Economics and Finance, 2023)
We evaluate the impacts of a randomized job-fair intervention in which jobseekers and employers can meet at low cost. The intervention generates few hires, but it lowers participants' expectations and causes both firms and workers to invest more in search as predicted by a theoretical model; this improves employment outcomes for less educated jobseekers. Through a unique two-sided belief-elicitation survey, we confirm that firms and jobseekers have over-optimistic expectations about the market. This suggests that, beyond slowing down matching, search frictions have a second understudied cost: they entrench inaccurate beliefs, further distorting search strategies and labour-market outcomes.
Keywords: O18; J22; J24; J61; J64; 330; job-search strategy; recruitment; matching; expectations; beliefs; reservation wage; youth unemployment; Ethiopia